Estructuras organizacionales en las Mipymes del sector de la construcción (2017)
This work was carried out in order to define the characteristics that the organizational structure to be implemented in the Smes of the construction sector should have in order to achieve success in the development of construction projects. It is intended to have a starting point so that small and medium entrepreneurs in the construction sector can have a pattern of how to shape their companies to take on the development of projects and that in turn companies are much more competitive and do not fail in the tried.